2010
DOI: 10.1111/j.1365-2753.2010.01545.x
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory sample turnaround times: do they cause delays in the ED?

Abstract: With the fastest 10% of samples being reported within 35 minutes (haematology) and 1 hour 5 minutes (biochemistry) of request, our study showed that delays can be attributable to laboratory TAT. Given the limited ability to further improve laboratory processes, the solutions to improving TAT need to come from a collaborative and integrated approach that includes strategies before samples reach the laboratory and downstream review of results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…On the other hand, they generally require deeper investigations, diagnostic tests, or laboratory studies, which lengthens their ED treatment stay. 36,44 Clinical acuity has therefore been extensively studied as an ED-LOS determinant, with a majority reporting that it is a significant ED-LOS determinant. 5,[7][8][9]11,12,18,21,22,[28][29][30] Very few studies have reported a non-significant effect, 31 with the findings in the present study support the majority of the literature in that clinical acuity was a significant determiner of ED-LOS.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, they generally require deeper investigations, diagnostic tests, or laboratory studies, which lengthens their ED treatment stay. 36,44 Clinical acuity has therefore been extensively studied as an ED-LOS determinant, with a majority reporting that it is a significant ED-LOS determinant. 5,[7][8][9]11,12,18,21,22,[28][29][30] Very few studies have reported a non-significant effect, 31 with the findings in the present study support the majority of the literature in that clinical acuity was a significant determiner of ED-LOS.…”
Section: Discussionmentioning
confidence: 99%
“…A limitation of the study was the use of aggregated hospital-level data without adjustments for patient and ED presentation-related characteristics. In addition, most of above studies only focused on a subset of laboratory tests, 7,8 rather than all requested laboratory tests. We aimed to address several of the limitations of previous studies by assessing the relationship between all laboratory test TATs on ED LOS across four hospitals.…”
mentioning
confidence: 99%
“…5 A simulation study by Storrow et al 6 in 2008 suggested that decreased TAT could improve ED efficiency and reduce ED LOS. A small single-site study that examined 101 blood tests at one ED over a short period (27 hours) by Gill et al 7 in 2012 showed an association between prolonged LOS and TAT. Francis et al in 2009 8 reported a relationship between laboratory work process design and LOS in ED, but they were unable show a direct relationship between TAT and ED LOS.…”
mentioning
confidence: 99%
“…13 Gill et al also showed a positive correlation between laboratory TAT and length of stay. 14 Regular monitoring of TAT itself acts as a very useful tool to improve the routine TAT as it aids to uncover and correct the unrecognised inefficiencies in laboratory operation. According to Peller GA et al daily monitoring and plotting of TAT in the form of freckle plot serves as a useful quality improvement tool.…”
Section: Before Intervention After Interventionmentioning
confidence: 99%